Module-scale simulation of forward osmosis module-part B: Modified Spiral-Wound - Muhammad Roil Bilad (Indonesian Journal of Science and Technology, 2017)
Forward osmosis (FO) is an attractive technology that offers advantages especially for treatment of challenging feeds in comparison to other membrane technologies. Substantial developments of membrane material have been shown recently. To support further development of FO process, a larger scale study via membrane module development is required to accurately envisage the most critical factors to be exploited to realize the promises. In this study, we applied a mass-transfer model coupled with the mass conservation and area discretization to simulate the performance of modified spiral-wound (MSW) modules (10 sheets of 1x1m). The study focuses on the spatial flux profile in a full-scale module as function of operational mode: co- vs counter cross current and membrane orientations (active-layer facing feed (ALFS); solution and active layer facing draw solution, (ALDS)). Results show that all modes offer almost similar average flux of about 9-10 L/m2h, but the co-current flows have much higher flux ranges (≈43%). The latter is expected to worsen membrane fouling resistant due to mal distribution in hydraulic loading. An operation with counter current and ALFS and counter current flow is then recommended because it offer similar flux but lower spatial flux ranges (7%).